Kartwelisches Wortgut - Fiihnrich , Heinz (Georgica, 2025)
* berg-: georg. brig-v-a ,,schlagen", swan. berg ,,Hacke". * bb,c>r-: georg. b,or-o ,,groBes, tiefes Loch, Hoh lung", swan. bter-i ,,groBes Loch". * wan-: georg. van- ,,Behausung, Wohnung", mingr. on- ,,Stadtname in Rats cha", swan. wan ,,Ebene, flacher Berg".